Structural and functional characterization of Cas2 of CRISPR-Cas subtype I-C lacking the CRISPR component - Anand, Vineet; Prabhakaran, Harshini Sheeja; Gogoi, Prerana; Kanaujia, Shankar Prasad; Kumar, Manish (Frontiers in Molecular Biosciences, 2022)
The genome of pathogenic Leptospira interrogans serovars (Copenhageni and Lai) are predicted to have CRISPR-Cas of subtypes I-B and I-C. Cas2, one of the core Cas proteins, has a crucial role in adaptive defense against foreign nucleic acids. However, subtype I-C lacks the CRISPR element at its loci essential for RNA-mediated adaptive immunity against foreign nucleic acids. The reason for sustaining the expense of cas genes is unknown in the absence of a CRISPR array. Thus, Cas2C was chosen as a representative Cas protein from two well-studied serovars of Leptospira to address whether it is functional. In this study, the recombinant Cas2C of Leptospira serovars Copenhageni (rLinCas2C, 12 kDa) and Lai (rLinCas2C_Lai, 8.6 kDa) was overexpressed and purified. Due to natural frameshift mutation in the cas2c gene of serovar Lai, rLinCas2C_Lai was overexpressed and purified as a partially translated protein. Nevertheless, the recombinant Cas2C from each serovar exhibited metal-dependent DNase and metal-independent RNase activities. The crystal structure of rLinCas2C obtained at the resolution of 2.60 Å revealed the protein is in apostate conformation and contains N- (1-71 amino acids) and C-terminal (72-90 amino acids) regions, with the former possessing a ferredoxin fold. Substitution of the conserved residues (Tyr7, Asp8, Arg33, and Phe39) with alanine and deletion of Loop L2 resulted in compromised DNase activity. On the other hand, a moderate reduction in RNase activity was evident only in selective rLinCas2C mutants. Overall, in the absence of an array, the observed catalytic activity of Cas2C may be required for biological processes distinct from the CRISPR-Cas-associated function.